Inter-band Bispectral Analysis of EEG Background Activity to Characterize Alzheimer's Disease Continuum - Maturana-Candelas, Aarón; Gómez, Carlos; Poza, Jesús; Ruiz-Gómez, Saúl J.; Hornero, Roberto (Frontiers in Computational Neuroscience, 2020)
The aim of this study was to characterize the EEG alterations in inter-band interactions along the Alzheimer's disease (AD) continuum. For this purpose, EEG background activity from 51 healthy control subjects, 51 mild cognitive impairment patients, 50 mild AD patients, 50 moderate AD patients, and 50 severe AD patients was analyzed by means of bispectrum. Three inter-band features were extracted from bispectrum matrices: bispectral relative power (BispRP), cubic bispectral entropy (BispEn), and bispectral median frequency (BispMF). BispRP results showed an increase of delta- and theta-interactions with other frequency bands, and the opposite behavior for alpha, beta-1 and beta-2. Delta- and theta-interactions with the rest of the spectrum also experimented a decrease of BispEn with the disease progression, suggesting these bands interact with a reduced variety of components in advanced stages of dementia. Finally, BispMF showed a consistent reduction along the AD continuum in all bands, which reflects an interaction of the global spectrum with lower frequency bands as the disease develops. Our results indicate a progressive decrease of inter-band interactions with the severity of the disease, especially those involving high frequency components. Since inter-band coupling oscillations are related with complex and multi-scaled brain processes, these alterations likely reflect the neurodegeneration associated with AD continuum.